THE IMPORTANCE OF SUCCESSFUL PROJECT TEAM COMMUNICATION IN AGRIBUSINESS - Langović Milicević, Ana; Tomašević, Vladimir; Isaković, Smiljka (Economics of Agriculture, 2014)
Agribusiness in the Republic of Serbia is on the very beginning of its preparations for European integrations. There is a need to modernize the organizational structure, change the approach to human resources management, and introduce project approach in the realization of tasks of all businesses in this industry. Project teams are crucial for the coordination of strategic management approach and the basis for organizational strengthening and productivity growth. If project approach is not implemented properly, organizations in agribusiness will not be able to cope successfully with needed reforms. The aim of this paper is to highlight the importance of successful communication of project team members in agribusiness industry which can help to improve motivation while avoiding or minimizing misunderstandings. To analyze the problem of project team communication in agribusiness we have conducted a research on a sample of 16 project managers and 98 project staff members.